2017
DOI: 10.4172/2168-9601.1000250
|View full text |Cite
|
Sign up to set email alerts
|

Brand Avoidance Motivators Stimulate to Brand Equity in the Mediating Role of Brand Hate: A Case of Smartphone Industry of Pakistan

Abstract: This study aims to examine the effect of brand avoidance motivators on brand equity. It also probes the mediating effect of brand hate among brand avoidance motivators and brand equity. In order to empirically study the above relationship the questionnaire was presently administered to the sample of 400 smartphone users. The 270 questionnaire were returned back. The received data was subjected to a number of statistical analyses. The finding proposed that brand avoidance motivators i.e., unmet expectations, sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 39 publications
(77 reference statements)
0
13
0
4
Order By: Relevance
“…Researchers agree that brand hate generated due to anger, disgust, and disappointment negatively affects consumer buying patterns, which leads to different behavioral responses like distraction ( Sampedro, 2017 ). Previous studies have confirmed that brand hate mediates the relationship between brand transgressions and anti-brand activism ( Romani et al, 2015 ), between brand avoidance and brand equity ( Abid and Khattak, 2017 ), and between perceived betrayal and anti-brand action ( Lee et al, 2013 ). Based on the above literature, we hypothesize that:…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations
“…Researchers agree that brand hate generated due to anger, disgust, and disappointment negatively affects consumer buying patterns, which leads to different behavioral responses like distraction ( Sampedro, 2017 ). Previous studies have confirmed that brand hate mediates the relationship between brand transgressions and anti-brand activism ( Romani et al, 2015 ), between brand avoidance and brand equity ( Abid and Khattak, 2017 ), and between perceived betrayal and anti-brand action ( Lee et al, 2013 ). Based on the above literature, we hypothesize that:…”
Section: Introductionmentioning
confidence: 81%
“…In certain conditions, similarity to competitor offer also generates a feeling of unwantedness thus generating a negative brand relationship. Sternberg (2003) found that negative emotions lead toward hate, which in turn has adverse effects on brand equity ( Abid and Khattak, 2017 ). If a brand fails to meet customer requirements, it creates a negative impact that further adversely affects brand equity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data was then analyzed on the SPSS software to run the regression for the purpose of finding the impact of predictors on the response variable. The equation formed on the basis of the proposed framework is :- To examine the combined effect of Predictors on the dependent variable, the analysis of variance test is used [21]. Table 3 is the ANOVA model which comprises of the variance analysis between after sale service, price, product, brand loyalty, product quality and purchase intentions.…”
Section: Methodsmentioning
confidence: 99%